Application of risk and reliability to the management of bridges - Onoufriou, Toula; Pardi, L.; Shetty, N. (My University, 2005)
Developments and application of risk and reliability methods in the field of bridge management are constantly increasing to face safety and security aspects within limited budget constraints. The level of maturity of these methods varies significantly between different sectors and countries and there is a lot of potential for technology transfer. This paper presents a study undertaken within the EU thematic network SAFERELNET which aims at evaluating the current level of applications of these methods for the highway sector compared to other sectors and countries. The main barriers of progress are identified and recommendations are made for further work required to promote these applications in order to reach the level of application of other industrial sectors and maximise the benefits from their use.
Keywords: Structural analysis (Engineering); Concrete bridges; Reliability